Optimizing large scale combinatorial problems using multiple ant colonies algorithm based on pheromone evaluation technique - Aljanaby, Alaa; Ku-Mahamud, Ku Ruhana; Md Norwawi, Norita (Dr. Sang H. Lee, 2008)
The approach of using multiple ant colonies is an extension of the Ant Colony Optimization framework. It offers a good chance to improve the performance of the ant algorithms by encouraging the exploration of a wide area of the search space without losing the chance of exploiting the history of the search.In this paper a new multiple ant colonies optimization algorithm is proposed. The new algorithm is based on the ant colony system and utilizes average and maximum pheromone evaluation mechanisms. The new algorithm can effectively be used to tackle large scale optimization problems.Computational tests show promises of the new algorithm.